Droganvändning och drogpreferenser bland universitetsstudenter vid LTU : En kvantitativ undersökning - Jansson, Nina (2014)
This is a study with quantitative method approach to investigate drug use and attitudes towards drugs among students at the Luleå Technical University. The aim was to describe and illustrate university students' use of and preferences towards drugs and drug use. To answer the aim of the study four questions were formulated; To what extent are students at LTU been offered drugs within the university? To what extent are students at LTU tried or uses drugs? What values, preferences and perspectives on drugs have students within LTU? Is there a tendency to normalization of drugs (cannabis) among students at LTU?Survey data collection was done by e- mail questionnaires to all program students at the university. The response rate was 31, 5 percent, in total 2251 students.The survey showed that the most common drug among students was cannabis. Students have been offered drugs by other students within the University. The most common drug offered was cannabis. The majority of the students showed a restrictive approach to drugs. Cannabis has not been normalized among the university students. However, a tendency toward normalization of cannabis was seen among program students at the university. Validerat; 20140617 (global_studentproject_submitter)